Wireless self-powered sensor networks driven by triboelectric nanogenerator for in-situ real time survey of environmental monitoring. (November 2018) - Zhou, Zhihao; Li, Xiaoshi; Wu, Yufen; Zhang, Heng; Lin, Zhiwei; Meng, Keyu; Lin, Zhiming; He, Qiang; Sun, ChenChen; Yang, Jin; Wang, Zhong Lin
Abstract: Reusing waste materials to create energy harvester will not just reduce the environmental pollution, but also generate renewable electricity by scavenging environmental energy to power wireless electronic devices, which will make our life more environmental friendly. In this study, we first turn waste milk carton into fully packaged arc-shaped triboelectric nanogenerator (AS-TENG) which can scavenge both wind and water flow energy for long-term wireless environmental monitoring. In general, the milk carton is laminated (from inside out) with a layer of polyethylene (PE), a layer of aluminum (Al) foil and a pulp layer. Such laminated material is suitable as the electrical unit of the AS-TENG. The arc-shaped design of AS-TENG is implemented to disrupt the flow, leading to vortex induced vibration, and thus contact electrification of the AS-TENG results in power generation. By optimizing the structural parameters systematically, the AS-TENG achieves an instantaneous peak voltage of 600 V, and a current of 40 μA. Moreover, a self-powered wireless environmental monitoring system using AS-TENG as power supply is developed for in-situ real time water quality (pH value) monitoring and landslide early warning in natural environment. This study provides solid progress toward the practical applications of TENGs in environmental monitoring. Graphical abstracts: Reusing waste materials to create energy harvester will not just reduce the environmental pollution, but also generate renewable electricity by scavenging environmental energy to power wireless electronic devices. In this study, an environmental friendly, multifunctional and fully packaged arc-shaped triboelectric nanogenerator (AS-TENG) by reusing waste milk carton is developed and capable of scavenging both wind and water flow energy efficiently. Moreover, a highly-integrated data acquisition, processing and wireless transmission monitoring system based on AS-TENG is established for real time and long-term water quality (pH value) monitoring and landslide early warning in natural environment. fx1 Highlights: The first environmental friendly triboelectric nanogenerator (TENG) reuses waste milk cartons for energy harvesting. The arc-shaped triboelectric nanogenerator (AS-TENG) with novel design is multifunctional and waterproof. The self-powered sensor system was developed using AS-TENG for long-term water quality monitoring and landslide warning.